2020
DOI: 10.3390/nu12082328
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variation in Human Milk Composition, a Systematic Review

Abstract: Background: Breastfeeding is considered the most optimal mode of feeding for neonates and mothers. Human milk changes over the course of lactation in order to perfectly suit the infant’s nutritional and immunological needs. Its composition also varies throughout the day. Circadian fluctuations in some bioactive components are suggested to transfer chronobiological information from mother to child to assist the development of the biological clock. This review aims to give a complete overview of studies examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 109 publications
4
74
0
7
Order By: Relevance
“…Consistent with prior studies of total fat [ 29 ], TAGs [ 39 , 49 ], and cholesterol [ 14 , 49 , 50 ] in human milk, we found that the concentrations of many species of glycerolipids, phospholipids, and sphingolipids were higher in the evening compared with the morning. By comparison, earlier studies have found that sterol lipids including cortisol and cortisone reach their peak in breastmilk in the morning [ 29 ], similar to the rhythm observed in blood plasma and saliva [ 19 , 51 ]. There is little evidence, however, that concentrations of free fatty acids exhibit diurnal variation in HM [ 29 ], which contrasts with results in blood plasma [ 52 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with prior studies of total fat [ 29 ], TAGs [ 39 , 49 ], and cholesterol [ 14 , 49 , 50 ] in human milk, we found that the concentrations of many species of glycerolipids, phospholipids, and sphingolipids were higher in the evening compared with the morning. By comparison, earlier studies have found that sterol lipids including cortisol and cortisone reach their peak in breastmilk in the morning [ 29 ], similar to the rhythm observed in blood plasma and saliva [ 19 , 51 ]. There is little evidence, however, that concentrations of free fatty acids exhibit diurnal variation in HM [ 29 ], which contrasts with results in blood plasma [ 52 ].…”
Section: Discussionsupporting
confidence: 91%
“…By comparison, earlier studies have found that sterol lipids including cortisol and cortisone reach their peak in breastmilk in the morning [29], similar to the rhythm observed in blood plasma and saliva [19,51]. There is little evidence, however, that concentrations of free fatty acids exhibit diurnal variation in HM [29], which contrasts with results in blood plasma [52].…”
Section: Intra-individual Variationmentioning
confidence: 70%
See 2 more Smart Citations
“…Likewise, in the human milk there are beneficial bacteria that are transferred to the newborn by breastfeeding, colonizing the gastrointestinal tract [6]. In addition, other studies suggest that some components of the human milk such as proteins, nucleotides, vitamins among others undergo diurnal variations in the same way the gut microbiota does in both mice and humans [4,7]. We believe in the human milk; these oscillations enhance the well-being of the breast-fed infant.…”
Section: Introductionmentioning
confidence: 87%